Effectiveness of Counseling Using MCH Handbook 2017ed to The Knowledge and Attitudes of Mothers About Monitoring Toddler Growth - Niken Purbowati; Dewi Nirmala Sari; Siti Masitoh (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Maternal and Child Health Handbook (MCH) is a book that integrates with maternal and child health reporting, has been introduced in Indonesia since 1993. Efforts to optimize child growth, midwives use the 2017 edition of MCH Handbooks for counseling. The MCH Handbook contains early detection information for infant growth, toddlers through the Z score growth Chart height-for-age, and weight-for-height to prevent stunting and to waste in children. The research aims to determine the effectiveness of the counseling using the MCH Handbook 2017 edition of the Book of knowledge and attitudes of mothers on the growth monitoring of toddlers. Research quasi-experiment with pre-test-post test control group design. Sampling techniques randomized assignment in the working area of Tambora District Puskesmas. Data analyzed using the Wilcoxon test, independent T-test, and Mann Whitney Test. There is a meaningful difference in the average knowledge score (P = 0,0001) and the attitude (P = 0,0001) of the mother on the measurement of the post-test-pre test between the treatment group and the control group. There is a higher score difference for the knowledge and attitude of mothers given intensive counseling using the MCH Handbook edition of 2017.